МӘМЛЕКЕТЛИК ТИЛ – БАСҚАРЫЎДЫҢ НЫЗАМЛАСҚАН ТИЛИ - Оразымбетов, А.Қ. (FAN va JAMIYAT, 2019)
The article is dedicated to giving the state status to the Karakalpak language, its historical and socio-political significance and practical implementation of the requirements of the law.